Involvement of Kommerell's diverticulae—a new anatomical risk factor for acute aortic syndrome progression and technical considerations. Issue 10 (30th October 2022) - Cook, Victoria; Singla, Animesh A; Herlihy, David; Chui, Juanita; Fisher, Charles; Puttaswamy, Vikram
Abstract: We present two cases of acute aortic syndromes (AAS), involving an aberrant right subclavian artery (ARSA) with associated Kommerell's diverticulae (KD). One of the cases involves a penetrating aortic ulcer in patients with an ARSA and KD and represents the first reported such case in the literature. Both cases progressed despite optimal medical therapy suggesting AAS with this anomalous anatomy needs a more aggressive operative approach. The involvement of KD in a patient with AAS appears to increase aortic disease progression and this anatomical variation should be considered another anatomical criterion that may place these patients at higher risk of complication. Progression during conservative management and waiting for the patient to be in the traditional safer 'sub-acute' time frame after presentation increased the eventual difficulty of the hybrid repair. A hybrid open-endovascular repair was utilized in all cases and is a safe and effective strategy for managing patients with ARSA and KD presenting with AAS.